2019
DOI: 10.5603/ah.a2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Management of hypertension in pregnancy — prevention, diagnosis, treatment and long-term prognosis. A position statement of the Polish Society of Hypertension, Polish Cardiac Society and Polish Society of Gynaecologists and Obstetricians

Abstract: Disclaimer: The position statement represent the views of the authors and were produced after careful consideration of the scientific and medical knowledge and the evidence available at the time of their dating. The authors and societies are not responsible in the event of any contradiction, discrepancy, and/or ambiguity between the position statement and any other official recommendations or guidelines issued by the relevant public health authorities, in particular in relation to good use of healthcare or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 218 publications
1
12
0
Order By: Relevance
“…We found that BP in euthyroid patients with HTN was affected by indicators that are common risk factors for CVD [9,29,30]. Similar data were obtained in the Hordaland Health Study [8].…”
Section: Discussionsupporting
confidence: 82%
“…We found that BP in euthyroid patients with HTN was affected by indicators that are common risk factors for CVD [9,29,30]. Similar data were obtained in the Hordaland Health Study [8].…”
Section: Discussionsupporting
confidence: 82%
“…The study included 70 healthy pregnant euthyroid women aged 30.53±4.51 (mean±SD) years (range 19–47 years), at 32.38±4.25 weeks of gestation and 22 healthy non-pregnant women aged 33.08±8.72 years (range 19–44 years). According to the current guidelines 13 14 , the upper acceptable limit of blood pressure was 140/90 mmHg, though in practice mean blood pressure of our study subjects was about 110–120/60–80 mmHg.…”
Section: Methodsmentioning
confidence: 68%
“…Maternal multiple organ failure was diagnosed in case of alteration of two or more organs with a score of ≥3 according to Sequential Organ Failure Assessment Score [ 17 ]. Hypertension and PE were diagnosed according to the guidelines of the Polish Society of Obstetricians and Gynecologists [ 18 ]. Body mass index (BMI) was calculated by dividing as the actual body mass by the square of the body height.…”
Section: Methodsmentioning
confidence: 99%